Hepatoblastoma in a Child With Early-onset Cirrhosis. Issue 1 (January 2019) - Bennett, Julie; Kirby-Allen, Melanie; Ng, Vicky; Waye, John S.; Chung, Catherine T.; Shaikh, Furqan
Abstract : Hepatoblastoma is the most common hepatic malignancy of childhood with known genetic predispositions and perinatal risk factors, with rare case reports occurring in the setting of cirrhosis. This case describes a young patient with cirrhosis attributed to early-onset hereditary hemochromatosis who was diagnosed with hepatoblastoma with uncommon histologic findings, evidence of chemotherapy resistance who ultimately succumbed to her disease. It is important to consider diagnoses beyond hepatocellular carcinoma in this scenario and consider early biopsy. With atypical histology, the tumor may respond poorly to conventional treatment and aggressive surgery or intensive therapy should be contemplated.